SEASONAL DISTRIBUTION OF TOTAL SUSPENDED MATTER IN SUMBAWA SEA - IGAG SWANDANA; Takahiro Osawa; I Nyoman Merit (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2011)
Distribusi Musiman Total Suspended Matter (TSM) di Laut Surnbawa (117